Assessing the impact of innovation and organizational culture on the work performance of employees: The case of Panombon Agri Ventures Inc. - Breva, Francis Lorenzo V. (Animo Repository, 2022)
This study discusses the impact of innovation and organizational culture towards the work performance of employees with Panombon Agri Ventures Inc. as the chosen company for the study. With the constant evolution and advancement of both innovation and organizational culture, the researchers would like to determine whether or not innovation and organizational culture plays an important role towards the work performance of employees and what effects these. This was accomplished by the researchers through a survey questionnaire that was gathered from 91 employees and managers of Panombon Agri Ventures Inc. The survey questionnaire was composed of 42 questions correlating with Innovation, Organizational Culture and Work Performance. Based on the results of the survey questionnaire, the following conclusions were drawn: Innovation and organizational culture significantly impact the work performance of employees. Thus, it is essential for organizations to effectively utilize these variables to significantly improve their business performance and operations.